Empowering Women of the Karangpawitan Majlis Taklim Through Utilizing Digital-Based Local MSMEs - Ani Siti Anisah; Iman Saifullah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Empowering women within the Majlis Taklim community and harnessing local digital-based MSMEs represent innovative and efficacious strategies aimed at enhancing women's welfare and economic autonomy. This approach not only fosters individual capacity development but also fortifies communities through digital-based marketing strategy training initiatives. Employing the Participatory Action Research (PAR) approach, the community service was executed within the Majlis Taklim Karangpawitan women's community, commencing with field transects in September, with training activities subsequently conducted in December 2022. The outcomes of this service endeavor can be delineated through the phases of activity planning, implementation, and evaluation. The service activities were bolstered by the participation of marketing experts who delivered training sessions on utilizing digital platforms for marketing purposes, enhancing skills in packaging goods attractively, and deploying digital platforms to market local products effectively. The overarching goal of this service intervention is to augment the creativity of the women's community, empowering them to produce innovative products, appealingly package them, label them appropriately, and market them via digital platforms. Ultimately, it is envisaged that these efforts will engender positive economic outcomes, thereby contributing to the overall welfare of the community.